DIAGNOSIS AND MANAGEMENT OF EXERCISE-INDUCED ANAPHYLAXIS: A LITERATURE REVIEW - Elhatra Settaf-Cherif; Katarzyna Malinowska; Layla Settaf-Cherif (International Journal of Innovative Technologies in Social Science, 2025)
Background: Exercise-induced anaphylaxis (EIA) is a rare, potentially life-threatening allergic reaction triggered by physical activity, with food-dependent (FDEIA) and food-independent forms. Understanding its pathophysiology, triggers, and co-factors is essential for accurate diagnosis and prevention.Aim: To summarize current evidence on the epidemiology, pathophysiology, clinical presentation, diagnosis, and management of EIA.Methodology: A literature review was conducted using PubMed and Google Scholar.Results: EIA accounts for 2.3-5% of anaphylaxis cases. It is mediated by IgE-triggered mast cell degranulation, with exercise altering gastrointestinal permeability, osmolarity, and pH, thereby lowering the threshold for allergic reactions. Common triggers include wheat, shellfish, and nuts, with co-factors such as NSAIDs, alcohol, and environmental extremes. Diagnosis is based on detailed history, targeted allergy testing, and, when needed, supervised exercise challenges. Management involves immediate epinephrine administration for acute episodes and long-term prevention through trigger avoidance, co-factor management, and patient education.Conclusions: EIA is an under-recognized but preventable cause of severe allergic reactions. Early recognition, appropriate diagnostic work-up, and a personalized management plan allow most patients to continue safe physical activity.